Crown Development of Cedrus deodara - Singh, S. P. (Indian Forester, 1982)
Crown development of trees in stands is a facinating study. Though its application in growth and yield estimation may not be simple but it may serve useful purpose in some specific management objectives like establishment of seed production areas and management of seed orchards, guide for thinnings etc. With the help regression developed for Cedrus deodara (deodar) tabular statements have been generated to predict crown width, number of trees/ha for normal density stands and minimum number of trees/ha for full canopy coverage.